Noncanonical Wnt5a‐Ca2+‐NFAT signaling axis in pesticide induced bone marrow aplasia mouse model: A study to explore the novel mechanism of pesticide toxicity. Issue 10 (6th April 2015) - Chattopadhyay, Sukalpa; Chatterjee, Ritam; Law, Sujata
ABSTRACT: According to case‐control studies, long‐term pesticide exposure can cause bone marrow aplasia like hematopoietic degenerative disease leading to impaired hematopoiesis and increased risk of aplastic anemia in human subjects. However, the exact mechanism of pesticide mediated hematotoxicity still remains elusive. In this study, we investigated the role of noncanonical Wnt signaling pathway, a crucial regulator of adult hematopoiesis, in pesticide induced bone marrow aplasia mouse model. Aplasia mouse model was developed following inhalation and dermal exposure of 5% aqueous mixture of common agriculturally used pesticides for 6 h/day for 5 days a week up to 90 days. After that, blood hemogram, marrow smear, cellularity, scanning electron microscopy, extramedullary hematopoiesis and flowcytometric expression analysis of noncanonical Wnt signaling components, such as Wnt 5a, fzd5, NFAT, IFN‐γ, intracellular Ca 2+ level were evaluated in the bone marrow hematopoietic stem/progenitor compartment of the control and pesticide induced aplasia groups of animals. Results showed that pesticide exposed mice were anemic with peripheral blood pancytopenia, hypocellular degenerative marrow, and extramedullary hematopoiesis in the spleen. Upon pesticide exposure, Wnt 5a expression was severely downregulated with a decline in intracellular Ca 2+ level. Moreover, downstream of Wnt5a, we observed sharp downregulation of NFATc2 transcription factor expression, the major target of pesticide toxicity and its target molecule IFN‐γ. Taken together, our result suggests that deregulation of Wnt5a‐Ca 2+ ‐NFAT signaling axis in the hematopoietic stem/progenitor compartment plays a crucial role behind the pathogenesis of pesticide mediated bone marrow aplasia by limiting primitive hematopoietic stem cells' ability to maintain hematopoietic homeostasis and reconstitution mechanism in vivo during xenobiotic stress leading to ineffective hematopoiesis and evolution of bone marrow aplasia. © 2015 Wiley Periodicals, Inc. Environ Toxicol 31: 1163–1175, 2016.